STUDY OF TRIAZOLE IRON(II) COMPLEXES, WITH NITRATE AND CHLORIDE COUNTER ANIONS INSIDE THE NATA DE COCO BIOPOLYMER - YULIANTI (NIM : 90510002); Pembimbing : Prof. Dr. Djulia Onggo., INA
Iron(II) complexes with triazole(L) ligand with chemical formula of [FeL3]A2, A= counter ion, are interesting compounds in which they have two possible magnetic behavior that can be changed by temperature, therefore they have potential application as sensor materials. At certain temperature they showed diamagnetic behavior and changed to paramagnetic when heated. The change of the magnetic properties normally accompanied by the change of distinc colour. In this research, the 1,2,4 triazole (H-trz) and 4-Amino-4H-1,2,4 triazole (NH2-trz) have been reacted with iron(II) nitrat and chloride salts inside the nata de coco. The formation of the complexes were indicated by violet color in the biopolymer thin film. The amount of complexes in nata de coco is around 1 to 7 mg/cm2 which is measured indirectly from magnetic suseptibility data of the complexes in the powder form. The [Fe(Htrz)]3Cl2 [Fe(NH2trz)]3Cl2, [Fe(Htrz)]3(NO3)2, [Fe(NH2trz)]3(NO3)2 complexes are diamagnetic with magnetic moments (mu)eff between 0,97 – 1,33 BM. The color indexes of each complexes were indicated by primer color percentages (Red, Green, Blue) as follows (68,46,37), (48, 37, 21), (51, 35, 19) dan (27,21,11) at room temperature. From all complexes, only the [Fe(NH2trz)]3(NO3)2 complex showed color changing from violet with %R = 65+3, %G = 44±2, %B = 33+3 at 30oC became colorless with %R = 69±3, %G = 59±1, %B = 38±2 at 95oC, The distinc color changing was indicated by the increased of green index of 15%. The color changing of the complexes at variable temperatures has been recorded by a video recorder. The program Xilisoft Video Converter Ultimate 6 has been used to convert the video to photos and program Image J Server has been used to obtained the RGB indexes.